An In-Depth Review of Viddhakarma in Ayurvedic Tradition (AYUSHDHARA, 2025)
Ayurveda describes a wide range of treatment modalities, including several unique procedures outlined in ancient texts, especially in the Sushruta Samhita. These include Shastra karma (surgical), Anushastra Karma (parasurgical), and Shasthi Upakrama (sixty other therapeutic approaches). Among them, Vedhana Karma is a notable technique in Shalya Chikitsa (surgical practice), with Siravedhana (venesection or bloodletting) regarded as a core component- just as Marma therapy constitutes a significant part of Shalya Chikitsa. Siravedhana is primarily a bloodletting procedure, and Viddhakarma is a more specific, smaller-scale form of this, primarily used as a Shoolaghna Chikitsa (pain-relief therapy). This article aims to explore the concept and clinical application of Viddhakarma through a scientific lens, drawing insights from classical Ayurvedic texts as well as contemporary literature, online resources, and clinical publications. Materials used in the practice of Viddhakarma, along with clinical protocols, have been compiled and presented based on both traditional references and the author's clinical experience. Viddhakarma has shown significant efficacy in treating Raktaja (blood-related) and Pittaja (Pitta-related) disorders, as well as conditions involving other Doshas and Dhatus. It works by releasing obstructed Vata, draining impure blood, clearing bodily channels, and ultimately relieving pain. Thus, Viddhakarma serves as a valuable therapeutic option for pain management across various clinical scenarios.